Hypocalcemia as a Cause of Complex Febrile Seizures in a Toddler. (14th July 2021) - Meesters, Kevin; Wassenberg, Tessa; Vanbesien, Jesse
Abstract : A 13-month-old boy had suffered three episodes of complex febrile seizures. At this admission, there were signs of hyperexcitability, such as Trousseau sign and QTc prolongation. A point of care blood gas analysis revealed severe hypocalcemia. Therefore, prior to administering intravenous calcium gluconate, we took blood samples to investigate the etiology of this hypocalcemia: magnesium, parathormone, and 25-hydroxyvitamin D. Since both parathormone and phosphate were significantly elevated and 25-hydroxyvitamin D was within the normal range, pseudohypoparathyroidism was diagnosed. After two years of follow-up, serum calcium had normalized in our patient under supplementation of vitamin D and calcium. He had been free of convulsions, although different febrile episodes had occurred.